2020
DOI: 10.1002/suco.201900450
|View full text |Cite
|
Sign up to set email alerts
|

Extended experimental and numerical investigations on constraint forces from imposed deformations

Abstract: Constraint forces are directly proportional to the stiffness of the system, so the size of the constraining force reduction depends on the ability of the system to reduce stiffness by the cracking of concrete, the plasticizing of reinforcement, or a time‐dependent process. Constraint forces can be differentiated in two cases: internal forces due to constraints that have the same or opposite action effects as the load in the relevant cross sections. For the first case, extensive experimental investigations have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…After the reinforcement started to yield, a residual amount of the redistribution of the internal forces could still be detected. The same finding was made in other studies 39,40 …”
Section: Nonlinear Numerical Evaluationssupporting
confidence: 90%
See 1 more Smart Citation
“…After the reinforcement started to yield, a residual amount of the redistribution of the internal forces could still be detected. The same finding was made in other studies 39,40 …”
Section: Nonlinear Numerical Evaluationssupporting
confidence: 90%
“…The same finding was made in other studies. 39,40 Figure 13 shows the tensile damage variable d t of the concrete, which represents the cracked areas of the concrete. Figure 14 shows the plastic strain of the reinforcing steel; it can be observed that the reinforcement in the span and in the support area started yielding.…”
Section: Moment Redistributionmentioning
confidence: 99%
“…The parameters for the effective creep ratio are the second moment of area and the material properties, where deviations can be seen. According to Berger et al, 22 it was experimentally found that the stiffness at low load levels is underestimated by analytical calculations. Furthermore, it has already been determined for the post‐tensioned test body, see Section 7.2.1, that the theoretical material properties do not correspond exactly to the experimental values.…”
Section: Test Resultsmentioning
confidence: 99%
“…V h , V w , and V l represent the depth, width, and length of the void respectively F I G U R E 3 The three-dimensional finite element model and the mesh generation distance of the pipe was refined. The three-dimensional eight-node reduced integral solid element (C3D8R) with hourglass control was used in the model, [14][15][16][17] and the reasonable sizes of the FEM and meshes were determined using sensitivity analysis. At a model width of 10 times the diameter of the pipe, the maximum and minimum mesh size was equal to 0.15 and 0.08 m respectively, so the boundary effect and the impact of the mesh size on the model results could be ignored.…”
Section: Model Descriptionmentioning
confidence: 99%